Particle number measurements within periodic technical inspections: A first quantitative assessment of the influence of size distributions and the fleet emission reduction. (December 2020) - Bainschab, Markus; Schriefl, Mario A.; Bergmann, Alexander
Abstract: The enforcement of more stringent type approval emission standards de facto mandate manufacturers to equip vehicles with particle filters, which reduces the particle number concentration in automotive emissions to levels below typical ambient concentrations. Soon, the overall automotive particle emissions will be dominated by highly emitting vehicles with malfunctioned after-treatment systems, making tests of in-service compliance with emission standards inevitable. These tests are especially relevant for diesel-powered vehicles because broken diesel particle filters can increase the particle emissions by several orders of magnitude. For spark-ignition vehicles, the possible effect is significantly lower, and the implementation of corresponding tests is technically challenging. In this paper, particle number concentration measurements at idle speed for the identification of vehicles with malfunctioned particle filters have been studied. The results from a dedicated measurement campaign indicate that low cost equipment can be used for the identification of highly emitting diesel vehicles. The effectiveness of under-discussion instrument specifications has been evaluated employing simulations based on measured particle size distributions. Finally, an assessment of the potential impact of particle number measurements during periodic technical inspections on the fleet emission was performed. The corresponding results demonstrate that the enforcement of these measurements can reduce the overall particle emissions of the actual fleet by more than 80%. Graphical abstract: Image 1 Highlights: Particle number emissions and size distributions at low and high idle speed. Validation of prototype diffusion charger devices. Assessment of particle size distributions' influence on PN measurement deviations. First quantitative impact assessment of PN PTI measurements on fleet emissions.